Salicylic acid had the potential to enhance tolerance in horticultural crops against abiotic stress - Chen, Shanshan; Zhao, Chun-Bo; Ren, Rui-Min; Jiang, Jun-Hai (Frontiers in Plant Science, 2023)
Horticultural crops are greatly disturbed by severe abiotic stress conditions. This is considered one of the major threats to the healthy lives of the human population. Salicylic acid (SA) is famous as one of the multifunctional phytohormones that are widely found in plants. It is also an important bio-stimulator involved in the regulation of growth and the developmental stages of horticultural crops. The productivity of horticultural crops has been improved with the supplemental use of even small amounts of SA. It has good capability to reduce oxidative injuries that occur from the over-production of reactive oxygen species (ROS), potentially elevated photosynthesis, chlorophyll pigments, and stomatal regulation. Physiological and biochemical processes have revealed that SA enhances signaling molecules, enzymatic and non-enzymatic antioxidants, osmolytes, and secondary metabolites activities within the cell compartments of plants. Numerous genomic approaches have also explored that SA regulates transcriptions profiling, transcriptional apprehensions, genomic expression, and metabolism of stress-related genes. Many plant biologists have been working on SA and its functioning in plants; however, its involvement in the enhancement of tolerance against abiotic stress in horticultural crops is still unidentified and needs more attention. Therefore, the current review is focused on a detailed exploration of SA in physiological and biochemical processes in horticultural crops subjected to abiotic stress. The current information is comprehensive and aims to be more supportive of the development of higher-yielding germplasm against abiotic stress.